ATMOSPHERIC PATTERNS OF EXTREME RAINFALL EVENTS IN THE EASTERN REGION OF THE STATE OF PARANÁ - de Bodas Terassi, Paulo Miguel; Galvani, Emerson; Baratto, Jakeline; da Silva Oscar-Júnior, Antonio Carlos (Ra'e Ga: o Espaço Geográfico em Análise, 2023)
Knowledge of the atmospheric patterns associated with the occurrence of extreme rainfall events can support the prediction of impacts, minimizing the human and material losses. Thus, this research evaluated the performance of the atmospheric systems responsible for the occurrence of extreme rainfall events in Curitiba and Paranaguá, eastern region of the state of Paraná. Data from different weather attributes recorded by conventional weather stations in both municipalities for the period between 1976 to 2015 were analyzed. The extreme rainfall events selected to apply the Rhythm Analysis (RA) were based on the use of the Ward’s method for the daily rainfall data which are greater than 99% of the percentiles. The Synoptic conditions responsible for extreme rainfall events were extracted from the synoptic letters provided by the Brazilian Navy and the “Technical Bulletin” of the Center for Weather Forecast and Climatic Studies. The RA showed that during winter there is the predominance of cold fronts and rainfall totals are spatially more homogeneous, while during summer there has a greater spatial difference, and the atmospheric conditions are frequently associated with the interactions of combination between tropical and extratropical systems.